SYNTHESIS OF NITROGEN-OXYGEN HETEROCYCLES FROM CARBOHYDRATE PRECURSOR - RAHMAN, M. ARDEL; SADEK, M. EL; BAKY , S. ABDEL; SOCCARY, N. EL (Biological Sciences - PJSIR, 2022)
6, 6-Dimethyl-4-oxo-4, 5, 6, 7-tetrahydroindol-2-carboxaldehyde (2) condensed with benzoylhydrazine to afford the corresponding benzoyl hydrazone derivative '3'. Oxidative cycJization of3 gave the corresponding 1,3, 4-oxadiaz<;>lemercuric complex '4'. On the other hand, the methylated aldehyde '5' condensed with a number of aryl and acylhydrazines to afford the corresponding hydrazones '6-18'. Oxidative cycJization of the acylhydrazones gave the corresponding 1,3, 4-oxadiazoles '19-27'. The structures were confirmed by rR, 1H-NMR and mass spectra.